2011
DOI: 10.1021/ja204387w
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Vesicles of Amphiphilic Gold Nanocrystals: Self-Assembly and External-Stimuli-Triggered Destruction

Abstract: We have developed a new class of plasmonic vesicular nanostructures assembled from amphiphilic gold nanocrystals with mixed polymer brush coatings. One major finding is that the integration of gold nanocrystals (nanoparticles and nanorods) with two types of chemically distinct polymer grafts, which are analogous to block copolymers as a whole, creates a new type of hybrid building block inheriting the amphiphilicity-driven self-assembly of block copolymers to form vesicular structures and the plasmonic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
276
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(279 citation statements)
references
References 48 publications
(25 reference statements)
2
276
1
Order By: Relevance
“…[44][45][46][47][48][49][50][51] However, so far there is no report about the nanovesicles based on amphiphilic fullerene derivatives for phototheranostics application. Therefore, it is of great interest to develop nanovesicles based on fullerene derivatives/PS and explore their cancer therapy efficiency as novel phototheranostic agents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51] However, so far there is no report about the nanovesicles based on amphiphilic fullerene derivatives for phototheranostics application. Therefore, it is of great interest to develop nanovesicles based on fullerene derivatives/PS and explore their cancer therapy efficiency as novel phototheranostic agents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In our case, the weight fraction of hydrophilic PEG in PEG and PNIPAM was 30%, and the ratio of the number of PEG to the number of nanoparticles was three, so we hypothesized that the amphiphilic HIC would lead to vesicles above the LCST of PNIPAM. Figure 1 shows the morphology of HIC at 37 • C. In the transmission electron microscopy (TEM) image ( figure 1(a)), one can see an obvious contrast between the interior and the shell of the particles, which was a characteristic image of hollow spheres as reported [16][17][18][19][20][21]. At a higher magnification, closely attached individual nanoparticles on the shell were visible, demonstrating that the vesicles were actually composed of individual AuNPs.…”
Section: Resultsmentioning
confidence: 78%
“…It has been reported that amphiphilic nanoparticles could self-assemble into vesicles [16][17][18][19][20][21]. A major strategy for the fabrication of amphiphilic AuNP is to covalently attach a copolymer or polymer mixture on the surface of gold nanocrystals [18-20, 22-24, 15, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…A key challenge for a wide range of future applications in photonics, bioimaging, and nanomedicine is the controlled spatial organization of QDs into hierarchical composite assemblies with targeted and complex functionality [1]. Several groups have met this challenge through the introduction of block copolymers or mixed polymer brush layers at the surfaces of QDs or other inorganic nanoparticles [6][7][8][9][10][11][12][13][14][15]. Chemically dissimilar polymer segments in the polymer layers are either specifically patterned or else undergo localized segregation on the nanoparticle surfaces, triggering anisotropic interactions in selective solvents and amphiphilic self-assembly into a variety of multiscale nanoparticle superstructures.…”
Section: Introductionmentioning
confidence: 99%